Daredevil (2016): back in black, volume 6 ebook Mayor fisk. - Gage, Christos (Daredevil (2016), 2018)
Collects Daredevil (2015) #595-600. New York has fallen to Wilson Fisk, the Kingpin of Crime: Daredevil's greatest and deadliest adversary is now the city's newly elected mayor! And the stage is set for their most unbelievable showdown yet. Matt Murdock has the law and his incredible abilities in his arsenal — but Fisk has an entire city on his side. As the mayor declares Daredevil Public Enemy No. 1, Matt Murdock receives the most incredible offer of his legal career! And while Fisk pursues a crusade against costumed vigilantes, a new player joins the resistance against him: the psychopathic murder artist Muse! Can Daredevil withstand assaults from both sides of this terrible conflict? As tensions build to a climax, the heroes and villains of New York's streets join the fray as the city is shaken to its very core